Neuromodulation of OCD: A review of invasive and non-invasive methods - Kammen, Alexandra; Cavaleri, Jonathon; Lam, Jordan; Frank, Adam C.; Mason, Xenos; Choi, Wooseong; Penn, Marisa; Brasfield, Kaevon; Van Noppen, Barbara; Murray, Stuart B.; Lee, Darrin Jason (Frontiers in Neurology, 2022)
Early research into neural correlates of obsessive compulsive disorder (OCD) has focused on individual components, several network-based models have emerged from more recent data on dysfunction within brain networks, including the the lateral orbitofrontal cortex (lOFC)-ventromedial caudate, limbic, salience, and default mode networks. Moreover, the interplay between multiple brain networks has been increasingly recognized. As the understanding of the neural circuitry underlying the pathophysiology of OCD continues to evolve, so will too our ability to specifically target these networks using invasive and noninvasive methods. This review discusses the rationale for and theory behind neuromodulation in the treatment of OCD.